Predictors for mortality in patients admitted with suspected bacterial infections – A prospective long-term follow-up study - Chafranska, Lana; Stenholt, Oscar Overgaard; Sørensen, Rune Husås; Abdullah, S.M. Osama Bin; Nielsen, Finn Erland (The American journal of emergency medicine, 2022)
The aim was to examine predictors for all-cause mortality in a long-term follow-up study of adult patients with infectious diseases of suspected bacterial origin. A prospective observational study of patients admitted to the emergency department during 1.10.2017–31.03.2018. We used Cox regression to estimate adjusted hazard ratios (aHR) with 95% confidence intervals for mortality. A total of 2110 patients were included (median age 73 years). After a median follow-up of 2.1 years 758 (35.9%, 95% CI 33.9–38.0%) patients had died. Age (aHR1.05; 1.04–1.05), male gender (aHR 1.21; 1.17–1.25), cancer (aHR 1.80; 1.73–1.87), misuse of alcohol (aHR 1.30; 1.22–1.38), if admitted with sepsis within the last year before index admission (aHR 1.56;1.50–1.61), a Sequential Organ Failure Assessment (SOFA) score ≥2 (aHR 1.90; 1.83–1.98), SIRS criteria ≥2 (aHR 1.23;1.18–1.28) at admission to the ED, length of stay (aHR 1.05; 1.04–1.05) and devices and implants as sources of infection (aHR 7.0; 5.61–8.73) were independently associated with mortality. Skin infections and increasing haemoblobin values reduced the risk of death. More than one-third of a population of patients admitted to the emergency department with infectious diseases of suspected bacterial origin had died during a median follow up of 2.1 years. The study identified several independent predictors for mortality.